Human-in-the-Loop Adaptive Control of an Ankle Exoskeleton for Gait Symmetry under Asymmetric Loading - Zhuang, Wenbing; Luo, Zining; Li, Xinying; Yu, Shiquan; Leng, Yuquan; Fu, Chenglong (IEEE/ASME International Conference on Advanced Intelligent Mechatronics, 2025)
Asymmetric weight-bearing frequently disrupts gait symmetry and increases muscular effort. This paper presents the development of a lightweight ankle exoskeleton and a human-in-the-loop (HIL) adaptive control strategy to mitigate these effects. The exoskeleton employs a modular design with remote actuation to minimize distal limb mass. The hierarchical control strategy estimates ankle joint moments in real-time using plantar pressure for proportional assistance, while a high-level Bayesian optimization algorithm iteratively adjusts bilateral assistance parameters to maximize a center of mass (CoM) velocity-based symmetry index (SI). Experiments with three healthy participants carrying a unilateral 15% body weight load demonstrated that the HIL optimization converged rapidly (average 2.8 min) to subject-specific, asymmetric assistance levels. Compared to unassisted loaded walking, the optimized assistance improved CoM velocity SI by 13.16%. Concurrently, bilateral plantar flexor muscle activation showed reductions of up to approximately 28%. These results highlight the potential of adaptive, personalized exoskeleton control to restore gait symmetry under asymmetric loading conditions.